1989
DOI: 10.1089/aid.1989.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Theoretically Determined Three-Dimensional Structures for Amphipathic Segments of the HIV-1 gp41 Envelope Protein

Abstract: Three-dimensional computer models for two segments of the C terminus of gp41, the transmembrane AIDS envelope protein, which may form amphipathic alpha-helices, have been generated using structure prediction techniques combined with energy minimization and molecular dynamics simulations. Regions gp41(772-790) and gp41(828-848) of the HXB2 strain of HIV-1 display extraordinarily high hydrophobic moment maxima as alpha-helices and when in an antiparallel conformation exhibit charge complementarity, implying that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 56 publications
1
65
0
Order By: Relevance
“…In contrast, the palmitoylated cysteine residues in the HIV-1 envelope cytoplasmic tail are about 59 and 132 amino acids away from the proposed membrane-spanning domain (41). However, there are two amphipathic regions in the cytoplasmic domain of the HIV envelope proteins, and it has been proposed that they could associate with the plasma membrane (42,43). The cysteine residues required for the palmitoylation of the HIV envelope protein are very close to these amphipathic regions.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the palmitoylated cysteine residues in the HIV-1 envelope cytoplasmic tail are about 59 and 132 amino acids away from the proposed membrane-spanning domain (41). However, there are two amphipathic regions in the cytoplasmic domain of the HIV envelope proteins, and it has been proposed that they could associate with the plasma membrane (42,43). The cysteine residues required for the palmitoylation of the HIV envelope protein are very close to these amphipathic regions.…”
Section: Discussionmentioning
confidence: 97%
“…Mutations in this domain may enhance Env fusion activity, but viral infectivity is greatly reduced in infected peripheral blood mononuclear cells, macrophages, and most T-cell lines (11,13,15,49). The three highly conserved amphipathic ␣-helical segments, designated lentiviral lytic peptide 1 (LLP)-1, LLP-2, and LLP-3, located in the C terminus of the cytoplasmic tail are thought to be associated with the inner surfaces of viral and cellular membranes (33,45). We previously showed that the multimerization potential and membrane binding ability of the cytoplasmic tail may play a crucial role in virus replication (3,5,7,28) and that the N-terminal segment of LLP-1 contains a structural determinant critical for modulating Env stability (27).…”
mentioning
confidence: 99%
“…The C terminus of the cytoplasmic tail may play a role in viral uncoating or penetration of the viral core into host cells (18). The large helical hydrophobic moments of the two segments spanning residues 828 -856 and 770 -795 (19,20), termed lentiviral lytic peptide (LLP)-1 and LLP-2, respectively, may have membrane-related functions (19). Structural modeling of these two regions reveals a high potential to form amphipathic ␣-helices (19 -21).…”
mentioning
confidence: 99%